Binder Jetting Additive Manufacturing: Spreading and Permeation of Multiple Micron Droplets in Porous Media. Issue 2 (15th December 2022) - Hu, Ankai; Huang, Yanlu; Chen, Zhiyi; Yang, Yongqiang; Xu, Yuxin; Wang, Tianyu
Abstract: The penetrating behavior of binder droplets has a substantial effect on the dimensional correctness and strength of the manufactured components. In this article, a physical model and a mathematical model of multiphase flow are created, computationally computed, and experimentally validated to predict the spreading and penetration behavior of multi‐drop binder in a powder bed. The findings indicate: 1) The spreading diameter and penetration depth of the binder increase as the number of droplets grows. However, the size of the rise reduces as the number of droplets grows. 2) The binder is spread symmetrically in the powder bed, with greater saturation in the middle area than margins on both sides, and a higher saturation in the upper region than the lower. 3) Repeated drops of binder in various areas may improve the saturation of the peripheral region while ensuring that the core area is not oversaturated. 4) It is discovered that as the number of ink jet drops rises, the size of the sample grows, and the growth in sample size reduces with the number of ink jet drops. This paper's findings provide light on the mechanics behind light‐cured binder jet additive manufacturing. Abstract : In this article, a physical model and a mathematical model of multiphase flow are created, computationally computed, and experimentally validated. The findings indicate: The spreading diameter and penetration depth increase as the number of droplets grows. As the number of drops rises, the size of the sample grows, and the growth in sample size reduces with the number of drops.